BUDAYA POLITIK MASYARAKAT SEDULUR SIKEP DALAM PEMILIHAN KEPALA DESA Studi Kasus Di Desa Larikrejo Kecamatan Undaan Kabupaten Kudus Tahun 2019 - Wahyuni, Tri; Ni’am, Harun (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2023)
The Sedulur Sikep community is a community group with traditional ties that are still strong and rooted in social life. They are scattered in various areas including in Larikrejo Village, Undaan District, Kudus Regency. Their average economic standard of living is still low, making it difficult to get them politically active. This affects their political culture, including in the 2019 village head election. This study aims to determine the political culture of the Sedulur Sikep community in the village head election and the factors that influence it. This study uses the theory developed by Gabriel A. Almond and Sidney Verba as an analytical framework. This theory explains cognitive, affective and evaluative orientations which are then categorized into types of political culture such as parochial, subject/subject, and participant. The results of the study show that the political culture of the Sedulur Sikep people belongs to the parochial type. The influencing factors are the level of education and economy, the traditional understanding of society which is obtained through the teachings of Saminism, feelings of inferiority towards state policies and changes to the order of the national political system